A new species of Dudgeodes Sartori, 2008 (Ephemeroptera: Teloganodidae) from Megamalai hills of southern Western Ghats, India - Srinivasan, Pandiarajan; Sivaruban, T.; Barathy, S.; Isack, Rajasekaran (Zootaxa, 2021)
Dudgeodes sartorii sp. nov. is described based on nymphs from the Megamalai hills of Western Ghats, Southern India. The nymph of Dudgeodes sartorii sp. nov. can be distinguished from other Indian species of Dudgeodes by i) prothorax with two rounded tubercles; (ii) outer margin of mesothorax with simple setae; (iii) distinct maculae in the distal region of femora; (iv) transverse row of setae on fore femora narrower with blunt apex and (v) dark brownish band on the 5th segment of cerci